Advances in experimental social psychology. Volume 23 - Zanna, Mark P.; ScienceDirect eBooks (San Diego ; London : Academic Press, 1990)
Each volume in Advances in Experimental Social Psychology contains an index, and each chapter includes references.
A continuum of impression formation, from category-based to individuating processes: influences of informationa nd motivation on attention and interpretation / Susan T. Fiske and Steven L. Neuberg -- Multiple processes by which attitudes guide behavior: the MODE model as a integrative framework / Russell H. Fazio -- PEAT: an integrative model of attribution processes / John W. Medeof -- Reading people's minds: a transformation rule model for predicting others' thoughts and feelings / Rachel Karniol -- Self-attention and behavior: a review an theoretical update / Frederick X. Gibbons -- Counterfactual thinking and social perception: thinking about what might have been / Dale T. Miller, William Turnbull, and Cathy McFarland.
Includes bibliographical references and indexes.
Print version record.
Elsevier
Keywords: Social psychology; Social psychology -- Research; PSYCHOLOGY -- Social Psychology; Social psychology; Social psychology -- Research; Electronic books